Evaluation of total, sn-2 fatty acid, and triacylglycerol composition in commercial infant formulas on the Chinese market: A comparative study of preterm and term formulas. (1st August 2022) - Yu, Jiahui; Wei, Wei; Wang, Fangmin; Yu, Renqiang; Jin, Qingzhe; Wang, Xingguo
Highlights: Total, sn -2 FA and TAGs composition of preterm and term formulas were analyzed. Preterm formula contained significantly higher C8:0 and C10:0. No significant differences of DHA existed. Preterm formula contained much lower C16:0 and C18:0 at sn -2 of TAG. High amounts of Ca-Ca-Cy and Ca-Ca-Ca existed in preterm formula. Abstract: Preterm infants with physiological immaturity require higher lipid provision than term infants. This study compared the lipid composition, including total, sn -2 fatty acid, and triacylglycerol (TAG) compositions in 14 preterm formulas and 25 term formulas in the Chinese market, in 2020–2021. Preterm formula had higher medium-chain fatty acid (MCFA) and comparable C22:6n-3 (DHA) contents than term formula. Notably, significantly lower C16:0 and C18:0 ( p < 0.001) were distributed on the sn -2 position in preterm formula. Two hundred and thirteen kinds of TAG molecular species were identified using UPLC-Q-TOF-MS. In preterm formula, significantly higher Ca-Ca-Cy and Ca-Ca-Ca ( p < 0.001) existed. These clear distinctions showed the challenge of the progress in preterm formula, such as DHA status, MCFA pattern, and TAG esterified with palmitic acid on the sn -2 position.